2000
DOI: 10.1111/j.1349-7006.2000.tb00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Effects of Coumaperine from Pepper on the Initiation Stage of Chemical Hepatocarcinogenesis in the Rat

Abstract: This study was designed to investigate the chemopreventive action of three natural products, coumaperine, aurapten and an extract from rosemary, against the initiation stage of rat hepatocarcinogenesis. Coumaperine has been isolated from white pepper as a naturally occurring antioxidative agent, but its potential modifying effects on carcinogenesis remain unclear. In experiment 1, a modification of the model developed by Tsuda et al. was applied, with assessment of numbers and areas of induced glutathione S-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…From this point, rats were fed a normal diet for 3 weeks until undergoing partial hepatectomy. Examination of liver tissue suggested RE may exert some protective antioxidant effects [44]. In accordance with this, use of Swiss mice exposed to 6 Grays (Gy) ionizing radiation (IR) in their liver once, followed by treatment with 1000 mg/kg RE fed orally, daily for 5 days suggested protective, antioxidant activity by RE.…”
Section: Anticancer Effects Of Rosemary Extract (Re): In Vivo Animmentioning
confidence: 95%
See 1 more Smart Citation
“…From this point, rats were fed a normal diet for 3 weeks until undergoing partial hepatectomy. Examination of liver tissue suggested RE may exert some protective antioxidant effects [44]. In accordance with this, use of Swiss mice exposed to 6 Grays (Gy) ionizing radiation (IR) in their liver once, followed by treatment with 1000 mg/kg RE fed orally, daily for 5 days suggested protective, antioxidant activity by RE.…”
Section: Anticancer Effects Of Rosemary Extract (Re): In Vivo Animmentioning
confidence: 95%
“…Increases in glutathione (GSH), an antioxidant, and reductions in lipid peroxidase (LPx), an oxidizing agent resulting in free radical production and cell damage, have been recorded in IR-induced mouse liver [45] and DMBA-induced mouse skin cancer [46,47] models treated with RE. Similarly, RE decreased glutathione-S transferase (GST) positive foci, which are associated with oxidative damage from the reduction of GSH [40], in a rat DEN-induced liver cancer model however, results were not significant and should be taken with caution [44]. …”
Section: Mechanisms Of Anticancer Effects Of Rosemary Extract (Re)mentioning
confidence: 99%
“…26) These compounds have inhibitory effects on rat colon carcinogenesis. Caffeic acid, 27) cathechol 27) and auraptene 28) have inhibitory effects on rat hepatocarcinogenesis. We treated rats with these chemicals for 2 weeks and performed gene expression analysis using a novel 3D-microarray system to assess the feasibility of establishing a bioassay system to predict carcinogenicity and chemopreventive activity of chemicals from effects on gene expression patterns.…”
mentioning
confidence: 99%
“…Inhibition of cell proliferation as observed through the reduction of PCNA was implicated in the chemopreventive action of this dietary agent [36]. In a DENAinitiated hepatocarcinogenesis study, coumaperine was shown to decrease the numbers of GST-P foci in male F344 rats.…”
Section: Coumaperinementioning
confidence: 99%
“…Auraptene was initially investigated for its chemopreventive actions by Kitano and co-workers [36]. Auraptene was initially investigated for its chemopreventive actions by Kitano and co-workers [36].…”
Section: Monoterpenesmentioning
confidence: 99%